1991
DOI: 10.1021/ma00023a030
|View full text |Cite
|
Sign up to set email alerts
|

Melting and recrystallization during mesophase transitions of a thermotropic liquid crystalline polymer

Abstract: Wide-angle X-ray diffraction (WAXD), polarized optical microscopy, and differential scanning calorimetry (DSC) have been employed to elucidate the mesophase transitions in a thermotropic liquid crystalline polymer (LCP) prepared by copolymerization of Bisphenol E diacetate, isophthalic acid, and 2,6-naphthalenedicarboxylic acid. A single glass transition temperature (T,) and double endotherms were discerned in the DSC scans of the neat LCP. The dual melting peaks, commonly attributed to the fast and slow melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Using the 73/27 HBA/HNA copolyester Lin and Winter42-43 reported that Tm 1 was higher than Tm2 in the range of annealing temperatures employed, whereas using the 58/42 HBA/ HNA copolyester Butzbach and co-workers46 observed that at low annealing temperatures, Tm 1 was lower than Tm2, but the value of Tm 1 increased rapidly with increasing annealing temperature and eventually exceeded the value of Tm2, yielding a cross-over. By examining the results reported in a paper by Kyu and co-workers45 (refer to Figure 1 in ref 45), we have noted that a cross-over between Tmi and Tm2 also occurred in their TLCP. A cross-over between Tm 1 and Tm2 seems to suggest that the location of Tmi, regardless of whether it is a high-temperature melting peak or low-temperature melting peak, depends on annealing conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Using the 73/27 HBA/HNA copolyester Lin and Winter42-43 reported that Tm 1 was higher than Tm2 in the range of annealing temperatures employed, whereas using the 58/42 HBA/ HNA copolyester Butzbach and co-workers46 observed that at low annealing temperatures, Tm 1 was lower than Tm2, but the value of Tm 1 increased rapidly with increasing annealing temperature and eventually exceeded the value of Tm2, yielding a cross-over. By examining the results reported in a paper by Kyu and co-workers45 (refer to Figure 1 in ref 45), we have noted that a cross-over between Tmi and Tm2 also occurred in their TLCP. A cross-over between Tm 1 and Tm2 seems to suggest that the location of Tmi, regardless of whether it is a high-temperature melting peak or low-temperature melting peak, depends on annealing conditions.…”
Section: Discussionmentioning
confidence: 73%
“…At still higher temperatures during annealing, the shift of the low‐temperature endotherm is much more than that during low‐temperature annealing. Nam et al17 observed that the premelting transition is a melting–recrystallization process. It is possible that during high‐temperature annealing near the melt transition, the positional ordering of the solid crystals might be disturbed so that the rigid macromolecules reorganize to form a new crystal structure and finally terminal melting to form a mesophase.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally not suitable for diols having aromatic or tertiary hydroxyl groups because of the poor nucleophilicity, competitive elimination reactions, and steric hindrance. In our studies, those polyesters derived from rigid aromatic diols (22)(23)(24)(25)(26)(27)(28)(29) were synthesized by the reaction with 2,2′-bipyridine-5,5′-dicarbonyl chloride (20) in the presence of pyridine. Polyesters with a flexible main chain or side chain were synthesized by transesterification reaction between diethyl-2,2′-bipyridine-5,5′-dicarboxylate (21) and the corresponding diols (30-38) with a catalytic amount of titanium(IV) isopropoxide.…”
Section: Synthesis Of Polymers Model Compounds and Their Correspondimentioning
confidence: 99%
“…4′-dihydroxybiphenyl(22), bisphenol A (23), 4,4′-dihydoxybenzophone(26), dihydroxypropiophenone(27), 2,7-dihydroxynaphthalene (28), 1,n-dihydroxyalkane (33a-i, n ) 2, 4, 5, 6, 7, 8, 9, 10, 12), 2,2-dimethyl-1,3-propanediol (36), 2,5-dihydroxybenzoquinone, and 6-chloro-1-hexanol were purchased from Lancaster Synthesis Ltd. 4,4′-(Hexafluoroisopropyliene)dianiline 6, 4,4′-ethylenedi-m-toluidine (15), 4,4′-(hexafluoroisopropyliene)-diphenol (24), 2,2-dimethyl-1,3-propanediol (35), 2-methyl-2-propyl-1,3-propanediol (37), and 2-butyl-2-ethyl-1,3-propanediol (38) were purchased from Aldrich Chemical Co. Inc. 2,2′-Bipyridine-5,5′-dicarboxylic acid (1), 2,2′-bipyridine-4,4′-dicar-…”
mentioning
confidence: 99%